AI-aided Design? Text-to-image Processes for Architectural Design (diségno, 2023)
Artificial Intelligence (AI) is marking a turning point in many aspects of human life, and it is appropriate to question its potential use in the architectural representation processes.This contribution provides a brief overview of the recent past of AI technologies to explain how they work, a snapshot of the current state of the art from text-to-image processes to image-to-3D processes, mainly focusing on the StableDiffusion platform.It also offers an overview of the latest studies in the field of architectural design. The subsequent experimentation becomes an opportunity to showcase the potential of AI in the co-creation process and the ability to simulate various graphic techniques, up to photorealistic visualization. On the other hand, it presents the limitations that, at the current stage of development, sometimes invalidate the results of text-to-image processes concerning the scientific aspects of representation.The conclusions reflect on the differences between human and artificial intelligence, the theme of shared authorship between humans and machines, and their consequences for architectural design.
Keywords: artificial intelligence; text-to-image; design drawing; authorship; stablediffusion